Carbonic anhydrase IX inhibitor S4 triggers release of DAMPs related to immunogenic cell death in glioma cells via endoplasmic reticulum stress pathway - Jing Cui; Huizhe Xu; Ji Shi; Kun Fang; Jia Liu; Feng Liu; Yi Chen; Haiyang Liang; Ye Zhang; Haozhe Piao (Cell Communication and Signaling, 2023)
Abstract Background Immunogenic cell death (ICD), which releases danger-associated molecular patterns (DAMP) that induce potent anticancer immune response, has emerged as a key component of therapy-induced anti-tumor immunity. The aim of this work was to analyze whether the carbonic anhydrase IX inhibitor S4 can elicit ICD in glioma cells. Methods The effects of S4 on glioma cell growth were evaluated using the CCK-8, clonogenic and sphere assays. Glioma cell apoptosis was determined by flow cytometry. Surface-exposed calreticulin (CRT) was inspected by confocal imaging. The supernatants of S4-treated cells were concentrated for the determination of HMGB1and HSP70/90 expression by immunoblotting. RNA-seq was performed to compare gene expression profiles between S4-treated and control cells. Pharmacological inhibition of apoptosis, autophagy, necroptosis and endoplasmic reticulum (ER) stress was achieved by inhibitors. In vivo effects of S4 were evaluated in glioma xenografts. Immunohistochemistry (IHC) was performed to stain Ki67 and CRT. Results S4 significantly decreased the viability of glioma cells and induced apoptosis and autophagy. Moreover, S4 triggered CRT exposure and the release of HMGB1 and HSP70/90. Inhibition of either apoptosis or autophagy significantly reversed S4-induced release of DAMP molecules. RNA-seq analysis indicated that the ER stress pathway was deregulated upon exposure to S4. Both PERK-eIF2α and IRE1α- XBP1 axes were activated in S4-treated cells. Furthermore, pharmacological inhibition of PERK significantly suppressed S4-triggered ICD markers and autophagy. In glioma xenografts, S4 significantly reduced tumor growth. Conclusions Altogether, these findings suggest S4 as a novel ICD inducer in glioma and might have implications for S4-based immunotherapy. Video Abstract